Protocols in semen biology (comparing assays) - Srivastava, N.; Pande, Megha (Springer, 2017)
This book on protocols in semen biology is a compilation of 20 chapters written by 15 experts from 5 Indian Council of Agricultural Research institutions, focusing on the basics of various procedures in semen biology with applications in animal and other allied sciences. The information is presented in simple language with illustrative figures and colour microphotographs, making it understandable for readers of every level. It highlights recent findings, the comparative analysis of assays, protocols, points to ponder, background information and major references, and also compares various assays for evaluating a seminal parameters. The book provides a comprehensive resource for beginners, as well as academics, investigators and scientists of animal semen biology and relevant fields. Further, it offers valuable teaching material.
Keywords: Semen.; elektronické knihy; electronic books